6. Zredukuj wyrazu podobne.

a) -2 -2a +3
b) 2a -3b +3a -2b
c)2y -6y +4x -2x
d) 2x +3 -6x -10
e) -x + 2x +(-6) + x -4
f) 2ab -6 -ab - (-3)
g) 3x² -2y² -6x² -2y²
h) 3,5b -2,4c -0,6c - 0,5b
i) 3x² -2x + 1 + x -4x² - 2
j) 2m² + 3mn -n +mn +3n -m²

2

Odpowiedzi

2010-02-23T19:16:42+01:00
A)-2a+1
b)5a-5b
c)-4y+2x
d)-4x-7
e)-x+2x-6+x-4=2x-10
f)ab-3
g)3x²
h)3b-3c
i)-x² -x-1
j)m²+4mn+2n
2 2 2
Najlepsza Odpowiedź!
2010-02-23T23:43:53+01:00
A) -2 -2a +3 = 1-2a
b) 2a -3b +3a -2b = 5a-5b
c)2y -6y +4x -2x = -4y+2x
d) 2x +3 -6x -10 = -4x-7
e) -x + 2x +(-6) + x -4 = 2x-10
f) 2ab -6 -ab - (-3) = ab-3
g) 3x² -2y² -6x² -2y² = -3x²-4y²
h) 3,5b -2,4c -0,6c - 0,5b = 3b-3c
i) 3x² -2x + 1 + x -4x² - 2 = -x²-x-1
j) 2m² + 3mn -n +mn +3n -m² = m²+4mn+2n
4 4 4